The uterus syndrome - breast - Kock, Walter (2015)
In reviewing texts and magazines Gynecology past we were surprised to see that intomática association with breast hypertrophy hypogenitalism adolescents had not escaped the trained "clinical eye" specialists from other eras. We can not hide the mosión while satisfaction we feel when we glimpse through these publications manifest interest and concerns that sparked this puzzling and bizarre symptomatic coincidence that later seemed paradoxical and which, perhaps for these reasons, not dared in assigning category and name syndrome.